A Retrospective Analysis of Oral Langerhans Cell Histiocytosis in an Iranian Population: a 20-year Evaluation - Atarbashi Moghadam, Saede (J Dent (Shiraz), 2015)
STATEMENT OF THE PROBLEM: Langerhans cell histiocytosis is a rare disease with unknown pathogenesis and is characterized by local or disseminated proliferation of Langerhans cells. There is no previous investigation on prevalence of oral Langerhans cell histiocytosis in Iranian population. PURPOSE: The purpose of this study was to assess the relative frequency of oral Langerhans cell histiocytosis in an Iranian population and to compare the data with previous reports. MATERIALS AND METHOD: Pathology files of Oral and Maxillofacial Pathology Department of Dental School of Shahid Beheshti University of Medical Sciences from 1992 to 2012 were searched for cases recorded as oral Langerhans cell histiocytosis. A total number of 20 cases were found and the clinical information of patients was recorded. RESULTS: The relative frequency of oral Langerhans cell histiocytosis was 0.34% and the most common location was the posterior mandible. In addition, the mean age of patients was 27 years and there was a definite male predominance. Most lesions were localized and tooth mobility was the most common oral presentation. CONCLUSION: In Iranian population as in many other countries, the relative frequency of oral Langerhans cell histiocytosis is low. Moreover, tooth mobility and periodontal lesions are the frequent early signs of disease. Therefore, in patients with periodontal problems, good oral health, and no response to the treatment; Langerhans cell histiocytosis must be considered. Additionally, although most cases of oral Langerhans cell histiocytosis are localized, systemic involvement must also be considered and dental professionals have an important role in early detection of the disease.